STRATEGI GURU AKIDAH AKHLAK DALAM MENINGKATKAN AKHLAKUL KARIMAH SISWA MTS MAFATIHUL HUDA AEK BATANG TORU - Nabila Ismi; Ardian Al Hidaya (Yayasan Baitul Hikmah al-Zain, 2024)
This article reveals the strategies used by Akidah Akhlak teachers at MTs Mafatihul Huda Aek Batang Toru to improve the moral character (akhlakul karimah) of class VII students. This research highlights various effective approaches such as personal interaction, interactive teaching methods, role modeling, integration of moral values ​​in subjects, extracurricular activities, and spiritual formation. However, teachers face challenges such as time constraints, curriculum pressure, environmental influences, and limited resources. Collaboration between school stakeholders—teachers, parents, and the community—is crucial in shaping holistic character development. Continuous evaluation of character education programs ensures significant positive impacts for future generations. The importance of collaboration between schools, teachers, parents and the community in supporting student character formation is also a main focus, with ongoing evaluation of character education programs to ensure a significant positive impact for future generations.